Hemp-lime as a tool for undergraduate research and teaching experiences - Hindman, Daniel P.; Hammett, Tom (Frontiers in Sustainability, 2025)
The continued growth of hemp-based products in construction is a subject that many students in the Sustainable Biomaterials department at Virginia Tech are interested in pursuing as a career. In response to this interest, the authors have conducted several special study courses and independent research activities with students to increase their understanding of hemp and other bio-based materials in construction. Experiential learning activities such as these are now in high demand, are being encouraged at Virginia Tech and are recognized as important by employers. The purpose of this article is to describe an evolution of educational activities and suggest best practices for other educators to help students gain experience with hemp-based products while preparing them for careers in construction. When discussing novel construction materials such as hemp-based products, there is often little information available as to the use and application of these in teaching and project learning. By using a combination of classroom lectures, laboratory activities, and active engagement with industry professionals, teaching professionals can be effective learning venues to prepare students for career paths.